Does Fiscal Policy Matter? A Study on Economic Crises in Indonesia - Prasasti, Sri Rejeki; Ekananda, Mahjus (JEJAK: Jurnal Ekonomi dan Kebijakan, 2023)
Fiscal policy is one of the instruments used by the government in dealing with economic crises. The recent COVID-19 pandemic crisis has different characteristics from the previous ones in  Indonesia. Hence, the fiscal policy needed is also different. Therefore, this study aims to know the role of fiscal policy shocks in affecting some macroeconomic indicators, including GDP, inflation, and interest rate, in Indonesia and investigate its differences within two periods: Period I (1993Q1-2018Q4), which includes the Asian Financial Crisis and the Global Financial Crisis, and Period II (2019M1-2021M12), which include the COVID-19 Pandemic crisis. This study employs the Structural Vector Autoregression (SVAR) model, using institutional information of the government budget system as restrictions. This study concludes that: 1) shocks in fiscal policies significantly affect GDP in both periods; 2) the dynamic movement of GDP is more influenced by government spending than government revenue; 3) fiscal policy, especially revenue, has greater influences on inflation during the COVID-19 Pandemic; 4) fiscal policy has a minor role in affecting the interest rate.